“Cancer changes everything, but it makes you wonder—am I still enough?” serial focus groups with adolescent and young adult cancer patients to understand experiences with cancer and sexual and reproductive health - Oveisi, Niki; Cheng, Vicki; Taylor, Dani; Kang, Preet; Brotto, Lori A.; Peacock, Stuart; McTaggart-Cowan, Helen; Hanley, Gillian E.; Gill, Sharlene; Rayar, Meera; Srikanthan, Amirrtha; Barnes, Mikaela; et al. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background The impacts of cancer and its treatment on sexual and reproductive health among adolescents and young adults (AYA, ages 15–39) are not understood. We conducted a patient-oriented, novel serial focus group study to explore the sexual and reproductive health experiences of AYA cancer patients during and beyond treatment. Methods Participants (≥ 18 years) who were diagnosed with cancer between 15 and 39 years and reside in Canada were assigned to respective focus group cohorts based on shared characteristics (e.g., gender, cancer stage). Each cohort participated in three serial focus groups that emulated support groups, fostering a sense of community. Focus groups were co-facilitated with a patient research partner (PRP) and guided by a topic guide co-created with PRPs. Framework analysis involving steps of familiarizing with transcripts, identifying thematic framework, indexing data sections by theme, extracting and organizing data into charts, and analyzing charts, were applied to transcripts. Results Altogether, 48 AYA cancer patients, divided into 8 cohorts, participated in a total of 24 focus groups. Cohorts included: cis-gender women (n = 10), 2SLGBTQIA+ (n = 7), Black, Indigenous, and People of Colour (BIPOC; n = 7), cis-gender men (n = 6), breast cancer (n = 6), pelvic cancer (n = 6), diagnosed during adolescence (ages 15 to 19; n = 4), and stage 4 (n = 3) (one individual participated in two cohorts). Cohorts had representation of nonbinary and gender fluid participants (n = 4), non-heterosexual sexual orientation (n = 14), and racial diversity (n = 12). The final framework encompassed two thematic areas broadly categorized as patients’ experiences (“what is happening to them”) and their responses (“how they are reacting or acting”). The first thematic area (three themes), focused inward on the direct effects of cancer and its treatment on patients’ sexual and reproductive health. The second thematic area (three themes), looks outward at the external impacts, capturing how cancer affects aspects of patients’ sexual and reproductive health, including relationships, societal expectations, and community support. Conclusion Uncovering the profound and complex personal and interpersonal impacts of AYA cancer on sexual and reproductive health, our study has important implications for informing appropriate and affirming support.